"Amphibious Power": The Law of Wreck, Maritime Customs, and Sovereignty in Richelieu's France. (12th October 2015) - Trivellato, Francesca
Abstract : The precise length of territorial waters, the swath of sea along the coast over which a state extended sovereign control, remained an object of debate during the seventeenth century. Some authors still adhered to the 100-mile boundary established by medieval glossators, whereas others embraced the so-called cannon-shot rule that set the limit to the reach of a shot fired from the land. But no one disputed the existence of territorial waters. Even Hugo Grotius (1583–1645), then Europe's greatest champion of the freedom of the sea, followed Roman law in conceding that a state could exert its sovereignty over littoral waters or inlets in a shoreline ( diverticula maris ). This rare point of agreement between theorists of mare liberum (the free sea) and defenders of mare clausum (the closed sea) did not eliminate all controversies concerning the governance of coastal waters. Particularly contentious were domestic and international disputes over the property rights on the cargo of sunken ships. What sources of law governed the assignment of ownership of salvaged wreckages? Who was entitled to compensation for assisting in the recovery efforts? And how did legal claims square with political maneuvering in domestic and interstate disputes over wreckages?